Cheiro de terra molhada de chuva para voz feminina e piano de Antonio Celso Ribeiro: uma abordagem interpretativa com ênfase em dinâmica e pedal - Wagner Sander Delmondes (2013)
In this paper we propose an interpretative options and choices the cycle off songs Cheiro de terra molhada de chuva for female voice and piano by the composer Antonio Celso Ribeiro and lyrics by poet Cintia Kallas. We also seek to show how the musical corpus chosen is inserted into the trend of New Simplicity, stylistic tendency that emerged in Germany in the late '70s, whose compositional and philosophical principles were adopted by the composer in the mid-90s. We thus confront its main features with the compositional material employed in the work in question. The suggestion was made by inserting interpretative elements of Western traditional music into the original score.